Association between MTHFR C677T polymorphism and cognitive impairment in patients with cerebral small vessel disease: a cross-sectional study - Wang, Qijin; Yuan, Cuihua; Zheng, Zhixiong; Chen, Caihua; Zhan, Xiao; Lin, Xiaodan (Frontiers in Aging Neuroscience, 2024)
Objective Cerebral small vessel disease (CSVD) is the most common vascular cause of cognitive impairment. This study aimed to explore the association between MTHFR C677T polymorphism and cognitive impairment in CSVD patients. Methods Demographic, medical, laboratory, cognitive evaluation, and MTHFR C677T polymorphism data were collected from CSVD patients admitted to our hospital between January 2019 and July 2023. Inclusion criteria for CSVD were based on the Standards for Reporting Vascular changes on Neuroimaging (STRIVE) criteria, with age ≥ 45 years. Binary logistic regression models were used to analyze risk factors associated with WMH and cognitive impairment. Results A total of 330 CSVD participants were recruited in this study, including 179 male and 151 female, with a median age of 64 years (interquartile range: 58–73 years). There were 185 patients (56.1%) with cognitive impairment, 236 patients (71.5%) with WMH, 89 patients (27.0%) with CMB, 87 patients (26.4%) with lacunes. All participants completed MTHFR polymorphism analysis, 149 cases (45.2%) of the CC genotype, 112 cases (33.9%) of the CT genotype and 69 cases (20.9%) of the TT genotype. Patients with TT genotype exhibited higher plasma homocysteine levels and more severe WMH and cognitive impairment (p < 0.001). Multivariable binary logistic regression model showed that WMH was significantly associated with age (p = 0.019), history of hypertension (p = 0.011), HHcy (p = 0.019) and MTHFR genotype (p = 0.041); while cognitive impairment was significantly associated with age (p = 0.033), history of hypertension (p = 0.019), HHcy (p = 0.040), MTHFR genotype (p = 0.039), WMH (p = 0.041), and lacunes (p = 0.001). Conclusion In this cross-sectional study, we investigated the association between MTHFR C677T polymorphism and cognitive function in CSVD patients. We found that MTHFR 677 TT genotype was an independent risk factor for the progression of WMH and cognitive impairment in CSVD patients.